KINERJA DAN MUTU PELAYANAN KEFARMASIAN DI PUSKESMAS BAQA DI KOTA SAMARINDA - Husnul Warnida; Sari Putri Pertiwi; Eka Siswanto Syamsul (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2021)
Community Health Center (puskesmas) is the basic service health facility in Indonesia. Community Health Center organizes individual health efforts and community health efforts that must be supported by a quality pharmaceutical care. Pharmaceutical care at health center must comply with Pharmaceutical Care Standards. This study aims to determine the performance and quality of pharmaceutical care at Baqa Health Center according to Permenkes no 74/2016 and Permenpan 14/2017. This research is a descriptive research. Respondents were 306 patients who received pharmaceutical care at Baqa Health Center. The data collected were patient satisfaction level, measurement of the average time for drug compounding, the average time for drug delivery and drug information administration, and the percentage of compliance with the service standards. The results showed that the quality of pharmaceutical care at Baqa Community Health Center was 93.33% in the good category, and the performance value of pharmaceutical care at the Baqa Community Health Center was 81.09 in the good category.